Analisis Unsur Intrinsik Pada Novel “Danur” Karya Risa Saraswati - Sri Yulistiani Viranti; Syifa Nurjamilah (Inovasi Pendidikan dan Anak Usia Dini, 2024)
This research aims to analyze the intrinsic elements in the novel “Danur” by SSsRisa Saraswati using descriptive qualitative method. The main focus of this analysis includes theme, character, plot, setting, point of view, language style, and mandate contained in the novel. The qualitative method was chosen because it allows researchers to explore the meaning and context of the text in depth, as well as understand the interaction between these elements in forming the whole narrative. The results of the analysis show that the main theme of the novel revolves around the supernatural experiences experienced by the main character, as well as the relationship between the real world and the supernatural world. The characters in “Danur” are built with strong details, creating interesting dynamics in a storyline that moves forward with several flashbacks. The time and place settings provide important context for understanding the conflict. The first-person point of view deepens the emotional experience of the main character, while the language style used creates an atmosphere that supports the theme of the story. This research is expected to contribute to the study of Indonesian literature, especially in understanding Risa Saraswati's works and the application of qualitative methods in literary analysis.